Pemanfaatan ekstrak daun miana (Coleus atropurpureus L. (Bent)) untuk meningkatkan respon imun benih ikan Nila (Oreochromis niloticus) - Resiska Ta'dung; Reiny A. Tumbol; Joppy D. Mudeng; Hengky J. Sinjal; Cyska Lumenta (Universitas Sam Ratulangi, 2023)
Treatment of diseases in fish farming generally uses synthetic chemicals and antibiotics, but long-term use is not recommended because of the impact on environmental pollution, antibiotic resistance (antimicrobial resistance/AMR), and residue accumulation in fish. Currently, research regarding the use of herbs as immunostimulants to control infectious diseases by increasing the immune response of fish in aquaculture is currently being carried out. One of the herbal plants that has the potential to control fish disease is the miana plant (Coleus atropurpureus L. (Bent). The aims of this research were to examine the effect of miana leaf extract in increasing the phagocytic activity of tilapia seeds and to determine the concentration of miana leaf extract that can increase phagocytic activity. The test material used was miana leaves and for the test fish were tilapia seeds weighing 3.42 â€“ 4.10 g. The leaves were separated from the stems, washed and crushed until smooth. Furthermore, the leaves were extracted by maceration method using 70% ethanol solvent. 50 g of leaves soaked in 250 mL of each solution or with a ratio of 1:5. The extract was then concentrated using a rotary evaporator to obtain a concentrated extract of 30% of the total extract. The results showed that the addition of miana extract in fish feed had a very significant effect on the phagocytosis activity of tilapia (p<0.01). The best results were achieved in fish treated with 2% concentrated miana extract/kg of feed with phagocytosis activity reaching 64.84% compared to the control which was 51.67%. Keywords: Miana plants, immune response, maceration, Nile tilapia Â